Governance communication and school development in Rural and remote areas of Lao PDR (2008)
This paper contributes to the current body of knowledge on development communication, governance, and education management by testing a typology of governance communication on school-based management. It applies the ideal type features of public governance communication at the community level in the case of school construction in rural and remote areas of Lao PDR. It answers the question: Are the features of community governance communication present in community-based school construction and maintenance? It sought to: determine features of community governance communication within the school construction and maintenance model; assess how governance communication is operatinalized in rural and remote communities in Lao PDR; and establish the functions of governance communication in community-based school construction and management.

The study was conducted in the provinces of Phongsaly, Luang Namtha, Attapeu, and Xekong, specifically in the districts of Samphan, Gnot Ou, Nalae, Buenhouka, Long Sanxay, Phouvong, Dakcheung, and Khaleum. Data on 30 villages under these districts were gathered. There were 120 key informant interviewees and Focus Group Discussion (FGD) participants.

The study found that public governance communication at the community level was operationalized as having the provision of basic services as its goal; having village development councils, NGOs, community/mass organizations, and communities as the primary stakeholders; possessing the core values of social capital information, transparency, and community participation; using educational services as its strategic thrust; employing interpersonal communication, community media, and social mobilization as media and methods; and making use of community action as its key messages.

The study empirically validates the features of community governance communication as provided in the proposed typology.
Keywords: Communication in rural development; Flor, Benjamina Paula Gonzales